PENGARUH PEMBERIAN FUNGI MIKORIZA ARBUSKULAR (FMA) TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TEMBAKAU (Nicotiana tabaccum L.) DI LAPANGAN - Parulian Sinaga; Edison Purba; Jonis Ginting (Jurnal Agroekoteknologi, 2014)
ABSTRACTThe growth and yield of a selected tobacco varieties (Nicotiana tabaccum L) treated withmycorhiza fungi arbuskular were evaluated in a field experiment. The aimed of the research was todetermine the effect of mycorhiza fungi on the growth and yield of several varieties of tobacco. Theresearch was conducted outdoor in the field at Balai Benih Penelitian Tembakau Deli Medan withaltitude of about 25 meters above sea level at the beginning of February until May 2012, with twotreatment factors. The first factors is Varieties of tobacco (Tobacco deli varieties F1-45, VirginiaTobacco varieties NC 95, Tobacco varieties Deli Deli-4), the second factors is mycorhiza fungiarbuskular (without mycorhiza fungi arbuskular, 15 g/plant, 30 g/plant and 45 g/plant). Theparameters measured were plant height, number of leaves, stem diameter, and sand leaf length. Theresults showed that mycorhiza fungi arbuskular showed the best results for the parameters of plantheight, and steam diameter. Varieties significant effect on the parameters of plant height, stemdiameter, sand leaf weight. Combination treatment with different varieties mycorhiza significanteffect on plant height and stem diameter.Keywords: Mycorrhiza, varieties, Nicotiana tabaccum.